Prevalence of Listeria monocytogenes in Wild Birds, Rodents and Bats From Nanga Merit, Kapit - Annastasia, Mathew (Universiti Malaysia Sarawak, UNIMAS, 2010)
Listeria monocytogenes is gram-positive and facultatively anaerobic bacteria. It is an important pathogen which caused listeriosis in both human and animals. This study is focusing on the prevalence of L. monocytogenes in three selected animals namely wild birds, rodents and bats from Nanga Merit, Kapit. Seventy four samples were tested. Seven samples had positive growth on CHROMagar Listeria and five samples had positive growth on PALCAM Listeria Selective Agar. Fraser Broth was used to enrich the samples. There were two types of medium used to culture the bacteria which were CHROMagar Listeria and PALCAM Listeria Selective Agar. Positive growths of L.monocytogenes on CHROMagar Listeria were blue-green colonies with white haloes. Meanwhile, the appearance of positive colonies on PALCAM Listeria Selective Agar is grey-green colonies with black haloes. The positive growths were further tested with biochemical tests. In this study, the biochemical tests which had been conducted were oxidase test, catalase test, Simmon’s Citrate test, triple sugar ion test and sulphide indole motility test. This study showed two samples had positive results for all biochemical tests while the others had atypical results.